Selective retina therapy for acute central serous chorioretinopathy. Issue 1 (15th June 2010) - Klatt, C; Saeger, M; Oppermann, T; Pörksen, E; Treumer, F; Hillenkamp, J; Fritzer, E; Brinkmann, R; Birngruber, R; Roider, J
Abstract : Aims: To evaluate selective retina therapy (SRT) as a treatment of acute central serous chorioretinopathy. Methods: 30 eyes of 30 patients with central serous chorioretinopathy of at least a 3 months' duration were recruited. 14 eyes were randomised to an SRT group (Q-switched neodymium-doped yttrium lithium fluoride (Nd:YLF) laser, wavelength 527 nm, t=1.7 μs, energy 100–370 μJ, spot diameter 200 μm, pulse repetition rate 100 Hz, ) and 16 eyes to a control group. After 3 months of follow-up, patients in the control group with persistence of subretinal fluid (SRF) were allocated to a cross-over group, treated with SRT and followed up for further 3 months. The main outcome measures were change of best-corrected Early Treatment Diabetic Retinopathy Study visual acuity (BCVA) and SRF. Results: At 3 months of follow-up, the mean (SD) improvement of BCVA was significantly greater after SRT than in the control group: 12.7 (7.2) versus 6.3 (8.9) letters (p=0.04). SRF had decreased significantly more after SRT as compared with that the control group: 203 (136) μm versus 41 (150) μm (p=0.005). In eight eyes allocated to the cross-over group, the mean BCVA had increased during 3 months of follow up before SRT by 1.4 (5.2) letters and continued to increase during 3 months following SRT by 7.4 (6.3) letters, while SRF increased by 39.5 (160.2) μm before SRT and decreased by 151.5 (204.9) μm after SRT. In six of the eight eyes, SRF had completely resolved 3 months after SRT. Conclusions: SRT appears to expedite functional recovery and the re-absorption of SRF as compared with that in untreated controls. A larger prospective, randomised phase 3 confirmative patient study is warranted. Trial registration number: NCT00987077